Defining key outcomes to evaluate performance of newborn screening programmes for cystic fibrosis - Munck, Anne; Southern, Kevin W; Castellani, Carlo; de Winter-de Groot, Karin M; Gartner, Silvia; Kashirskaya, Nataliya; Linnane, Barry; Mayell, Sarah J; Proesmans, Marijke; Sands, Dorota; Sommerburg, Olaf; Barben, Jürg (Journal of cystic fibrosis, 2021)
To present signs and symptoms and clinical course in cystic fibrosis patients with false-negative newborn screening (CF NBS). - All children presented in this paper were covered by CF NBS. The group of 1.869.246 newborns was screened in the Institute of Mother and Child in Warsaw within a period of 01.01.1999 - 31.05.2019. Screening protocols evolved over time from IRT/IRT to IRT/DNA/EGA. - The authors identified 11 patients with false-negative NBS, in whom CF was diagnosed based on clinical symptoms or the examination of siblings with positive CF NBS. In the study group, the diagnosis was made significantly later in comparison to positive CF NBS patients ranging from 2 months to 15 years of age. CF NBS strategy does not significantly affect the sensitivity of the screening. - In the presence of clinical symptoms, additional diagnostics must be implemented, in spite of the negative screening results. At first, the sweat test should be conducted, followed by a DNA analysis of the most common mutations in the given population. The diagnostic process requires searching for CFTR mutations not typically associated with a high chloride concentration in sweat. Repetition of sweat chloride concentration enables the diagnosis in children whose initial chloride values in sweat are borderline, and no CF-causing mutations are detected. In strong clinical indications, the extension of DNA analysis (EGA) is recommended in order to identify rare CF variants. In children with meconium ileus, genetic analysis is mandatory. - Newborn screening for Cystic Fibrosis (CF) is associated with situations where the diagnosis of CF or CFTR related disorders (CFTR-RD) cannot be clearly ruled out. - We report a case series of 23 children with unconclusive diagnosis after newborn screening for CF and a mean follow-up of 7.7 years (4-13). Comprehensive investigations including whole CFTR gene sequencing, in vivo intestinal current measurement (ICM), nasal potential difference (NPD), and in vitro functional studies of variants of unknown significance, helped to reclassify the patients. - Extensive genetic testing identified, in trans with a CF causing mutation, variants with varying clinical consequences and 3 variants of unknown significance (VUS). Eighteen deep intronic variants were identified by deep resequencing of the whole CFTR gene in 13 patients and were finally considered as non-pathogenic. All patients had normal CFTR dependent chloride transport in ICM. NPD differentiated 3 different profiles: CF-like tracings qualifying the patients as CF, such as F508del/D1152H patients; normal responses, suggesting an extremely low likelihood of developing a CFTR-RD such as F508del/TG11T5 patients; partial CFTR dysfunction above 20% of the normal, highlighting a remaining risk of developing CFTR-RD such as F508del/F1052V patients. The 3 VUS were reclassified as variant with defective maturation (D537N), defective expression (T582I) or with no clinical consequence (M952T). - This study demonstrates the usefulness of combining genetic and functional investigations to assess the possibility of evolving to CF or CFTR-RD in babies with inconclusive diagnosis at neonatal screening. - Previous studies suggest that PAP-based CF protocols are suitable for newborn screening (NBS) for cystic fibrosis (CF) when newborns designated as CFSPID should not be detected. However, there are still discussions about the performance of IRT/PAP algorithms. We present the final results of a pilot study evaluating a IRT/PAP protocol with an IRT-dependent safety net (SN) conducted from 2008 to 2016 in southwestern Germany on nearly 500,000 newborns. - To achieve reliable data, all newborns were screened using both the PAP-based and a DNA-based CFNBS algorithm. PAP quantification and genetic analysis of the four most common CFTR mutations in Germany were performed in all newborns with IRT≥99.0 percentile. NBS was rated positive if either PAP was ≥1.6 µg/l and/or at least one CFTR mutation was detected. In addition, an IRT-dependent SN resulted in positive rating for both protocols if IRT was ≥99.9 percentile. To evaluate the IRT/PAP protocol, its performance was compared to that of the IRT/DNA protocol. - The IRT/PAP protocol with IRT-based SN used in the study achieved a sensitivity of 94%, if false-negative detected neonates with meconium ileus and those designated as CFSPID were excluded from analysis. CF/CFSPID ratio was 92. However, PPV of the IRT/PAP+SN protocol was with 10.3% very low. - PAP-based CFNBS protocols can be used, if less detection of CFSPID is desired. The IRT/PAP protocol with IRT-dependent SN evaluated here achieved adequate sensitivity but should probably be used in combination with a third-tier test to also achieve an acceptable PPV.